2003
DOI: 10.1016/s0014-5793(03)00474-5
|View full text |Cite
|
Sign up to set email alerts
|

NDR family of AGC kinases – essential regulators of the cell cycle and morphogenesis

Abstract: The nuclear Dbf2-related (NDR) family of protein serine/threonine kinases comprises mammalian NDR and large tumor suppressor (LATS) kinases, their orthologs from Drosophila melanogaster and Caenorhabditis elegans, and a number of related kinases from yeast and plants. The members of this family were independently implicated in various aspects of the control of cell division and morphogenesis. They are crucial regulators of the actin and tubulin cytoskeletal organization during polarized growth and cytokinesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 58 publications
0
128
0
Order By: Relevance
“…The sequences also contained an insert of 56 amino acids between subdomains VII and VIII, and three conserved Ser/Thr residues (Fig. 3), being characteristic of the Ndr family of eukaryotic protein kinases (Tamaskovic et al 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences also contained an insert of 56 amino acids between subdomains VII and VIII, and three conserved Ser/Thr residues (Fig. 3), being characteristic of the Ndr family of eukaryotic protein kinases (Tamaskovic et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Ndr is a conserved and widely expressed nuclear protein kinase, first isolated and sequenced in humans, D. melanogaster and C. elegans (Millward et al 1995). Although an entire signal transduction cascade in which Ndr is involved has not yet been elucidated, Ndr is considered to be important for the regulation of cell growth, cell division and cell morphology (Millward et al 1999, Tamaskovic et al 2003. In the present study, three cDNA clones encoding a Ser/Thr protein kinase which is homologous to Ndr, were isolated by data mining of the wheat EST database KOMUGI, and the primary structure of these cDNAs was determined by RT-PCR and the 5′-RACE method.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the lack of dependencies in localization, the occurrence of cells with SIN phenotype in pdk1⌬ cultures suggests that Pdk1p might modulate SIN function positively. In particular, it is interesting to note that Sid2p is related to members of the AGC family of kinases (Sparks et al, 1999;Tamaskovic et al, 2003) which are known to be regulated by PDK1 family members (Belham et al, 1999). However, the finding that SIN proteins participate in correcting defects associated with the cell division apparatus (Le Goff et al, 1999;Liu et al, 1999;Mishra et al, 2004) might provide an alternate explanation to the observed synthetic lethality between pdk1⌬ and SIN mutants.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, there are two human homologues of dtrc, NDR1 and NDR2. The kinase domains of LATS1 and NDR1 are 52% identical, whereas LATS2 and NDR1 are 54% identical [42]. By over-expressing or suppressing human NDR1 by siRNA, the kinase has been shown to regulate centrosome duplication during the cell cycle [43].…”
Section: Ndrmentioning
confidence: 99%